PENINGKATAN HASIL BELAJAR SISWA DALAM KETERAMPILAN MENULIS TEKS EKSPOSISI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW KELAS X IPS 4 SMA NEGERI 4 BUKITTINGGI TAHUN AJARAN 2016/2017 - Osmimi Osmimi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This study aims to obtain data and information about the application of the Jigsaw Cooperative Learning Model to improving learning outcomes in writing exposition texts of class X IPS 4 Bukittinggi Public High School 4 2016/2017 academic year. This type of research is Classroom Action Research (CAR) conducted in two cycles. The subjects of this study were students of class X IPS 5, amounting to 36 people consisting of 17 male students and 19 female students. The technique of collecting data uses observation, observation, and tests. The data obtained is then analyzed to draw conclusions. The results of this study can be seen from the increase in the initial precycle average with a percentage of completeness of 38.9%, after the first cycle increased to 75%, while the percentage of completeness in the second cycle increased significantly to 95%. The implication of this research is that the application of the Cooperative Learning Jigsaw Model can improve the learning outcomes of writing exposition texts of class X IPS 4 students at Bukittinggi 4 Public High School.